The Potential Advantage of Myo‐Inositol as a Dietary Supplement for Juvenile Hybrid Grouper (Brown‐Marbled Grouper Epinephelus fuscoguttatus ♀ × Giant Grouper Epinephelus lanceolatus ♂). (24th November 2021) - Zhu, Zhanhao; Li, Rimei; Yang, Qihui; Tan, Beiping; Dong, Xiaohui; Chi, Shuyan; Liu, Hongyu; Zhang, Shuang
Abstract: An 8‐week feeding trial was conducted to estimate the optimum dietary myo ‐ inositol (MI) requirement for juvenile hybrid grouper (Brown‐marbled Grouper Epinephelus fuscoguttatus ♀ × Giant Grouper E . lanceolatus ♂ ). Myo‐inositol was supplemented at 0 (control group), 150, 300, 600, 900, 1, 200, and 2, 000 mg/kg of diet. Basic diet contained no MI. Each diet was randomly fed to quadruplicate groups of juveniles, and each tank was stocked with 30 fish (initial weight = 7.40 ± 0.01 g [mean ± SD]). Results showed that the addition level of MI exerted no significant effect on the survival rate, feed conversion ratio, or protein efficiency ratio of juvenile grouper ( P  > 0.05). However, the weight gain rate in the 150‐mg/kg group was significantly higher than that in the control group ( P  < 0.05). The total cholesterol levels in the serum of the control and 150‐mg/kg groups were significantly higher than those of the other groups, and the triglyceride level in the 150‐mg/kg group was significantly lower than those in the other groups. The glutamine aminotransferase level was significantly higher in the control group than in the supplemented groups, but no significant difference in lysozyme activity was observed. In the liver, superoxide dismutase activity in the control group was significantly lower than that in the 150–900‐mg/kg groups, and the total antioxidant capacity in the 150‐mg/kg group was significantly higher than those in the other groups. Broken‐line regression analysis showed that the MI required for juvenile hybrid grouper was 181.47 mg/kg diet based on weight gain rate, which can significantly improve growth performance and increase the activity of serum and liver enzymes.